Nature and Methodology of Islamic Economics: An Appraisal (The Pakistan Development Review, 1992)
Islamic economics emerged as a discipline separate from the general science of economics in the wake of the political process of Islamisation of the Pakistani society and economy during 1977-88. In formulating its fundamental principles, Islamic economics seeks to fuse Islamic religion with economic science; that is, it tries to combine the study of economic phenomenon of ordinary business of life with religious beliefs, ethical norms, moral ideals, rules and laws, thus putatively believing that the social science of economics is a secular discipline which does not concern itself with value judgements, and that Islamic economics is a plausible alternative to modern economics since it is based on the values, norms and principles of Islam. [Ahmed (1981), p. xiv; Chapra (1985), pp.19-29).]